PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUICK ON THE DRAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DIKELAS X SMA NEGERI 1 BUNUT KABUPATEN PELALAWAN - Sri Wahyuni Sri Wahyuni; Elva Yasmi Amran Yasmi Amran; Rasmiwetti ' ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research about application of cooperative learning quick on the draw model to increase student’s achievement on the topic of hydrocarbon in class X SMA Negeri 1 Bunut had done in May 2014. The purpose of this research was to know increase student achievement in hydrocarbon topic by application of cooperative learning model quick on the draw and to know category increased student achievement on the topic of hydrocarbon in class X SMA Negeri 1 Bunut. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, whereas X3 as experiment class and X4 as control class mentioned randomly after normalitas and homogenates test were done. Experiment class was given treatment with quick on the draw model of cooperative learning while the control class wasnot given of cooperative learning quick on the draw model. The result of hypothesis test was tarithmetic > ttable ( 3.83 > 1.67), it means that the of application quick count on the draw model of cooperative learning can improve students learning achievement on hydrocarbon subejct at X SMA Negeri 1 Bunut. Category increased student achievement on experiment class including high with the normalized gain scores (N-gain) about 0,70.Keywords: Quick on the draw, Learning achievement and Hydrocarbon